Self-Regard in Pastoral Ministry: Self-Compassion versus Self-Criticism in a Sample of United Methodist Clergy. Issue 1 (March 2020) - Lee, Cameron; Rosales, Aaron
Pastoral ministry is a demanding and stressful vocation, and the empirical and anecdotal literature on ministry has often emphasized this negative outlook. More recent work, however, has shifted toward a more positive emphasis on personal characteristics that might help pastors be more resilient. The present study examined the interplay of identity demands, social support, and self-regard in accounting for both positive (positive affect and life satisfaction) and negative (negative affect and burnout) outcomes. Self-compassion, which was measured using the short form of Neff's (2003) Self-Compassion Scale (SCS-SF), was herein reconceptualized as being comprised of two types of self-regard: self-compassion and self-criticism. Regression analyses with data collected from 200 United Methodist pastors indicated that social support and self-compassion (in descending order of importance) explained a significant proportion of the variance of the positive outcome, while self-criticism, social support, demand, and gender explained the negative.